HUBUNGAN ANTARA KEMANDIRIAN BELAJAR SISWA DENGAN KEMAMPUAN KOMUNIKASI MATEMATIS MENGGUNAKAN UJI KORELASI: KORELASI - Puspa sugiarto; Tahta Alfiana P; Elika Budiarti; Fitriyah Amaliyah (MathVisioN, 2024)
This research uses quantitative research which aims to find out whether there is a significant relationship in the sense of whether there is a negative or positive relationship between learning independence and students' mathematical communication skills in class IV SD 4 Karangbener using the Correlation Test. The population in this study were all fourth grade students at SD 4 Karangbener, and a sampling technique was carried out by taking a sample of 17 students. The instrument is a test to obtain data regarding Mathematical Communication Ability in flat material. In this study, a correlation test was used to determine the relationship between student learning independence and students' mathematical communication skills using a questionnaire. The data analysis technique in this research uses a correlation test, where before carrying out data analysis, the data is first subjected to a normality test and linearity test to see whether the data is normally and linearly distributed. The result of the research is a significant relationship between student learning independence and students' mathematical communication skills in class IV SD 4 Karangbener with a calculated t value of correlation coefficient (r) of 0.21 with a coefficient of determination (KP) obtained as a result of 44.1 %.